Expanded HIV testing in high‐prevalence areas in England: results of a 2012 audit of sexual health commissioners. Issue 4 (31st October 2013) - Hartney, T; Kennedy, I; Crook, P; Nardone, A
<x xml:space="preserve">Abstract</x> Objectives The aim of the study was to examine whether UK HIV testing guidelines which recommend the expansion of HIV testing in high HIV prevalence areas have been implemented in England. Methods An online survey tool was used to conduct an audit of sexual health commissioners in 40 high HIV prevalence areas (diagnosed prevalence > 2 per 1000) between May and June 2012. Responders were asked to provide details of expanded HIV testing programmes that they had commissioned in nontraditional settings and perceived barriers and facilitators involved in introducing expanded testing. Results The response rate was 88% (35 of 40). Against the key audit standards, 31% (11 of 35) of areas had commissioned routine testing of new registrants in general practice, and 14% (five of 35) routine testing of general medical admissions. The majority of responders (80%; 28 of 35) had commissioned some form of expanded testing, often targeted at risk groups. The most common setting for commissioning of testing was the community (51%; 18 of 35), followed by general practice (49%; 17 of 35) and hospital departments (36%; 13 of 35). A minority (11%; four of 35) of responders had commissioned testing in all three settings. Where testing in general practice took place this was typically in a minority of practices (median 10–20%). Most (77%; 27 of 35) expected the rate of HIV testing to increase over the next year, but lack of resources was cited as a barrier to testing by 94% (33 of 35) of responders. Conclusions Not all high HIV prevalence areas in England have fully implemented testing guidelines. Scale‐up of existing programmes and continued expansion of testing into new settings will be necessary to achieve this.